New Technologies, Established Ideas: Drone Cameras and the Privacy Torts - Moreham, NA (Victoria University of Wellington Law Review, 2023)
This article considers what the challenges posed by drone camera technology tell us about the desirable operation of the New Zealand privacy torts. It highlights, in particular, the importance of recognising the normative nature of the reasonable expectation of privacy test, of considering the claimant's signals that observation was unwelcome when applying it, and of ensuring that privacy protection extends beyond publication of private information.